The Role of the Arctic Economic Council in the International Legal Framework of the Arctic Ocean Environmental Governing - A. N. Vylegzhanin; N. V. Korchunov; A. R. Tevatrosyan (Московский журнал международного права)
INTRODUCTION. The article covers the legal aspects of the establishment of a new international forum – the Arctic Economic Council – and its role in the existing international legal framework for governing the Arctic Ocean, including the Arctic seas. The status and the functioning of the said international forum, particularly with regard to the activities within its Working Groups, have been examined based on the analysis of the documents adopted by the forum since its establishment. Special attention has been paid to the legal analysis of the coordination of the newly established forum with the Arctic Council and the prospects of such institutional cooperation.MATERIALS AND METHODS. The research done by the authors on the relevant documents released by the Artic Council, in the context of legal and scientific sources on the topic of the Arctic Ocean and its seas, as well as on the Reports of the Arctic Economic Council submitted to the Senior Officials of the Arctic Council, underlies this article. The article also takes into consideration political and legal research of the Arctic Council’s work, aimed at the sustainable development of the economic activities in the region, as well as respective archive documents from the electronic database of the Arctic Council, including relevant press releases.RESEARCH RESULTS. The Arctic Economic Council (AEC), established upon the initiative of the Arctic Council in 2014, is a new circumpolar business-forum, which aims at fostering the sustainable development of the Arctic region by substantive cooperation with the entrepreneurs, carrying out economic activities in the region or planning to do so. The new international organization has the potential to become an effective international legal mechanism to promote greener economies in the Arctic; meanwhile, the organization is yet to become a constructive platform for dialogue on fostering the economic activities in the region.DISCUSSION AND CONCLUSIONS. The AEC foundational documents determine the structure and the course of action of the organization. The article, nevertheless, suggests that the executives and the Secretary of this newly established international forum ensure that the business representatives, committed to conduct activities in the Arctic, seek to comply with the international environmental standards, applicable to the Arctic; particularly that, subject to the unique vulnerability of the Arctic environment, an exchange of best practices takes place. Moreover, in view of the increased shipping and growth of other marine activities in the region, the Arctic business standards not only need to be more environmentally oriented, but also take into account the possibility of diversifying the Arctic economy. The AEC could focus its efforts on enhancing the quality of the regional regulation of the economic activities in the Arctic, paying particular attention to the coordinated self-regulative measures of the legal entities in different countries. In this case, its activities may prove to be more relevant and effective.